Safety of the effective radiation dose received during stroke hospitalization - Canton,Gregório Platero (2021)
Abstract Background Neuroimaging is widely used for diagnosis and treatment of stroke. However, little is known about whether the radiation doses received by patients comply with international safety guidelines. Objectives The aim of this study was to evaluate the effective radiation dose received while in hospital for stroke and analyze its safety according to current guidelines. Methods This cross-sectional study included 109 patients who were hospitalized and diagnosed with ischemic stroke. The National Institutes of Health Stroke Scale was used to evaluate stroke severity, the Bamford clinical classification was used for topography, and the TOAST classification was used for etiology. The computed tomography dose index and size-specific dose estimates were used to calculate the effective radiation dose (ERD) received while in hospital. A Mann-Whitney test was used to compare the ERD received by thrombolysed and non-thrombolysed patients. Non-parametric statistics were used to analyze the data with a 95% confidence interval. Results During the study period, the median ERD received was 10.9 mSv. Length of stay was not associated with radiation exposure. No differences were demonstrated in ERD according to stroke etiology or Bamford clinical classification. Patients who had CT perfusion (only or in addition to CT or angiotomography) received the highest ERD (46.5 mSv) and the difference compared to those who did not (10.8 mSv) was statistically significant (p<0.001). No differences were found in the ERD between thrombolysed and non-thrombolysed patients. There was no correlation between ERD while in hospital and stroke severity. Conclusions According to the current national guidelines, the protocol for examining images at our stroke unit is safe in terms of the ERD received by the patient while in hospital. There was no difference in the ERD received by patients stratified by thrombolytic treatment or stroke severity.